Atividades investigativas e abordagem contextual no contexto da sala de aula - Souza, Suelaine dos Santos (2019)
The use of Investigative Activities (AI) in teaching science aims to facilitate the understanding of scientific knowledge, as well as allows teaching to be directed towards the development of students' cognitive abilities. Investigative activities evoke the accomplishment of procedures like elaboration of hypotheses, data analysis and the development of the capacity of argumentation. In addition to the use of AI, the insertion of the History of Science through the study of historical episodes allows us to understand that scientific knowledge is not isolated from the socioeconomic, historical and cultural context. Considering these themes, this work aimed to investigate with aspects of Investigative Activity can be mobilized in a group of students who have experienced a Thematic Workshop approach on the insertion of a Contextual Approach and built on an investigative bias. The data collection was done through a didactic proposal (Thematic Workshop) in two schools of Greater Aracaju within the framework of the activities of the Institutional Program of Initiation to Teaching Scholarship. The subjects of the research were students of basic education, the data being collected through audiovisual recording and questionnaires. Data were analyzed according to qualitative treatment based on content analysis. As a result of this study, we verified some aspects of the nature of science and of scientific doing in the development of AI, as a proposition of a problem, elaboration of hypothesis, strategies to solve the problem, record of the collected data and conclusion of the problematic. It was also evident the development of attitudinal competences, in which the student is led to think, reflect, reason, using the argumentation and proposition of ideas.